A Necessary Deepening in Researching about non Transmissible Diseases - Raidel González Rodríguez (Revista Finlay)
Non transmissible diseases represent one of the most important challenges for the sanitary systems, particularly at the primary health care level. They have resulted in an increment in the incidence of patients, steady increase of its associated mortality and disability, so as a determining factor in economic costs, admissions and medical treatment. At the primary care level important activities for the control of these diseases, based mainly in actions of sanitary promotion, prevention of risks, comprehensive care, so as the rehabilitation of the associated sequel. This has enabled a more objective approach of its epidemiological-clinical behavior, higher quality assistance work so as an ascending research task.